The Mechanism of the International Labour Office in Monitoring Workers' Rights - Fordjan, Tayeb (Journal of Legal Studies and Researches, 2017)
The role of the International Labour Office in the protection of workers' rights is derived from the tasks entrusted to the ILO. It forms the backbone of the devices of this organization, and considering the organization of an international specialized agency of the United Nations are active in the social sphere givers have upgrade and the development of international labor law, through the creation of an international labor legislation helps to unify the international labor standards that guarantee the rights of workers to the states, whatever the nature of their political systems, as the widespread branches of the international Labour Office effectively contributed to making the international Labour Organization are available on the effective mechanism has enabled it to reduce the violation workers' rights in many countries.